Physical Development in Early Childhood - Fauziah Nasution; Winda Lestari; Cindri Madelta; Sofi Mayla Humairah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
Physical development in early childhood is a complex and significant process in a child's life. In this age range, children experience rapid body growth, gross and fine motor development, as well as changes in the nervous system and body organs. Genetic, environmental, and nutritional factors play key roles in directing the course of this physical development. A deeper understanding of these stages can help parents, educators and child health professionals provide appropriate support to ensure optimal growth and development in children during this critical period. At this age, fine and gross motor skills develop rapidly, allowing children to perform daily activities such as drawing, writing, and playing sports more skillfully. Environmental factors such as sensory stimulation and play opportunities also contribute to children's physical development and social skills. Therefore, a comprehensive understanding of the dynamics of physical development in early childhood can help create an environment that supports their holistic growth.